HSP90 Inhibitor 17-AAG Attenuates Nucleus Pulposus Inflammation and Catabolism Induced by M1-Polarized Macrophages - Zhang, Shuo; Wang, Peng; Hu, Binwu; Liu, Weijian; Lv, Xiao; Chen, Songfeng; Shao, Zengwu (Frontiers in Cell and Developmental Biology, 2022)
Overactivated inflammation and catabolism induced by proinflammatory macrophages are involved in the pathological processes of intervertebral disc (IVD) degeneration (IVDD). Our previous study suggested the protective role of inhibiting heat shock protein 90 (HSP90) in IVDD, while the underlying mechanisms need advanced research. The current study investigated the effects of HSP90 inhibitor 17-AAG on nucleus pulposus (NP) inflammation and catabolism induced by M1-polarized macrophages. Immunohistochemical staining of degenerated human IVD samples showed massive infiltration of macrophages, especially M1 phenotype, as well as elevated levels of interleukin (IL)-1β, tumor necrosis factor (TNF)-α and matrix metalloproteinase (MMP)13. The conditioned medium (CM) of inflamed NP cells (NPCs) enhanced M1 polarization of macrophages, while the CM of M1 macrophages but not M2 macrophages promoted the expression of inflammatory factors and matrix proteases in NPCs. Additionally, we found that 17-AAG could represent anti-inflammatory and anti-catabolic effects by modulating both macrophages and NPCs. On the one hand, 17-AAG attenuated the pro-inflammatory activity of M1 macrophages via inhibiting nuclear factor-κB (NF-κB) pathway and mitogen-activated protein kinase (MAPK) pathways. On the other hand, 17-AAG dampened M1-CM-induced inflammation and catabolism in NPCs by upregulating HSP70 and suppressing the Janus Kinase 2 (JAK2)-Signal Transducer and Activator of Transcription 3 (STAT3) pathway. Moreover, both in vitro IVD culture models and murine disc puncture models supported that 17-AAG treatment decreased the levels of inflammatory factors and matrix proteases in IVD tissues. In conclusion, HSP90 inhibitor 17-AAG attenuates NP inflammation and catabolism induced by M1 macrophages, suggesting 17-AAG as a promising candidate for IVDD treatment.